Optimisation of mix proportion for repair mortar modified with mineral and chemical admixtures - Ahmed, Md. Muheeb; Umar, Mohd; Ahad, Ahmed Abdul; Mohammed, M.S. Haji Sheik (Journal of Structural Engineering, 2024)
A study was carried out in order to develop optimum combinations of repair composite for the repair and rehabilitation of distressed Reinforced Concrete (RC) structures. The study comprises of two phases viz. phase I and II. In phase I, the optimisation of mineral admixed composites using Taguchi’s technique was performed. The results were analysed using ANOVA and the optimum mineral admixed composites with better performance in strength was used in phase II which deals with the evaluation of synergistic effect of mineral admixtures with chemical admixtures. Based on the analysis of Taguchi’s technique and ANOVA with minimal experimental validation, it was found that metakaolin (MK) based mineral admixed composites offered better strength performance as compared to silica fume (SF) based mineral admixed composites. It can be said that, Taguchi’s technique with ANOVA can be effectively used to optimize cement-based repair composites involving varied mineral and chemical admixtures. A study on the synergistic effect of optimised mineral admixtures with chemical admixtures showed positive influence in all the tested dosage irrespective of the type of admixture. The analysis of test results revealed the optimum dosage of tested chemical admixtures as 2% by weight of cement. The durability studies on optimised mineral - chemical admixed composites exhibited significantly improved performance for sodium nitrite based mixed inhibitor (SNM) composites followed by styrene acrylate copolymer (AR) and acrylic ester and styrene-based polymer (SAR) composites and SEM analysis also confirms the same. Based on the findings of strength and durability studies, the performance of optimised mineral - chemical admixed repair composites was graded as; SNM > AR > SAR with 15% MK and silica powder as cement and sand replacement material respectively.